An investigation into the association between plantar distal phalanx angle and hindlimb lameness in a UK population of horses. (30th September 2019) - Clements, P. E.; Handel, I.; McKane, S. A.; Coomer, R. P.
Summary: Low heels are the most common hoof conformational abnormality seen in both the front and hind feet of horses. A low/negative distal phalanx angle in the front feet has been associated with palmar heel injuries but only recently has the significance of low/negative angles in the hind feet received attention. A study including a greater number of horses more representative of the UK horse population would be useful to UK equine practitioners. Our null hypothesis was that the plantar distal phalanx angle does not differ between horses with and without hindlimb lameness. For this prospective case‐controlled study, horses presenting for orthopaedic complaints underwent a complete lameness assessment. The plantar distal phalanx angulation (PDPA), the angle between a line parallel to solar surface contacting the ground and the solar margin of the distal phalanx, was calculated from lateromedial radiographs. Horses were included in the study if hindlimb lameness was definitively localised by diagnostic anaesthesia. Student's t ‐tests and multivariable linear regression models were used for statistical analysis. One hundred and eighty‐two horses met the inclusion criteria, 132 with hindlimb lameness and 50 controls. The mean left PDPA for HLL group was −1.0° vs. +1.8° for the controls. The mean right PDPA for HLL group was −1.1° vs. +1.4° in controls (both P<0.001). Lameness was most frequently localised to the stifle (59% of horses), followed by the distal tarsal joints and the proximal suspensory region. A limitation of the study was that the control group included some forelimb lame horses. It was concluded that horses with hindlimb lameness, including lameness localised to the stifle, were more likely to have negative PDPAs. While Pezzanite et al . (2019) previously reported a relationship between negative/neutral PDPA and tarsal/metatarsal lameness, this study is the first to find a relationship to stifle lameness, which may reflect differences in the populations of horses examined. Further kinematic studies are required to determine whether it is a cause or effect relationship.